A research to approach and understand to heritage from the perspective of diversity - Marín Cepeda, Sofía (Pulso. Revista de educación, 2013)
Around 15% of the population according to the World Health Organization, have some kind of disability. Our social reality is complex, and social awareness of this issue in recent decades has had a huge impact on education, where difference and diversity leads to a necessary change in edu¬cational methods. The concern and the search for a social space and a comprehensive educa¬tional approach for all extends, beyond the formal environment, to the experiences of education in heritage spaces. This opening represents a diver¬sification of educational approaches to address individual differences in the pursuit of common objectives. One of the great challenges facing us from our research, therefore, is to generate equal¬ity on the possibility of linking heritage and people. Our research, doctoral thesis in the field of herit¬age education from the University of Valladolid, is characterized by addressing the learner from his/her psychological dimension and diversity, to design an educational model in order to generate equality in the ability linking heritage and people.
Keywords: Heritage Education; Diversity; Psychology; Research; Education Model